3
$\begingroup$

If $\log _b a\cdot\log_c a +\log _a b\cdot\log_c b+\log _a c\cdot\log_b c=3$ and $a,b,c$ are different positive real numbers not equal to 1, then find the value of $abc$.

I tried to simplify this by different methods like using the identity $\log_b a=\frac{1}{\log_a b}$, but I couldn't get anywhere. Addition, subraction can't be used. I am not able to figure out a way to simplify the LHS. It would be great if someone could help me to proceed with this problem.

$\endgroup$
  • 5
    $\begingroup$ Hint: $\log_a b = \frac{\ln b }{\ln a}$. Apply this to all terms, then simplify using log rules. $\endgroup$ – John Hughes Dec 15 '16 at 12:43
1
$\begingroup$

We can write $\log_{b}a = \frac{\log a}{\log b}$ and similarly $\log_{c}a = \frac{\log a}{\log c}$. Expanding like this, we have, $$\log_ba\log_ca + \log_ab\log_cb + \log_ac\log_bc =3$$ $$\Rightarrow \frac{(\log a)^2}{\log b\log c} + \frac{(\log b)^2}{\log a\log c} + \frac{(\log c)^2}{\log a\log b} =3$$ $$\Rightarrow \frac{(\log a)^3 + (\log b)^3 + (\log c)^3}{\log a\log b\log c} =3$$ $$\Rightarrow (\log a)^3 + (\log b)^3 + (\log c)^3 = 3\log a\log b\log c...(1)$$ Let $\log a =x, \log b=y, \log c =z$. Then equation $(1)$ transforms to $$x^3+y^3+z^3 = 3xyz \Leftrightarrow x+y+z=0$$ Then, $$\log a+\log b+\log c=0$$ $$\Rightarrow \log abc =0$$ $$\Rightarrow abc =10^0=1$$ Hope it helps.

$\endgroup$
  • 4
    $\begingroup$ Also: the fact that $x+y+z = 0$ solves the equation doesn't mean that every solution has the property that $x +y+z = 0$. $\endgroup$ – John Hughes Dec 15 '16 at 13:02
  • $\begingroup$ That double-implication is not the result of transforming the previous equation as claimed; it's a separate result, and requires justification. $\endgroup$ – John Hughes Dec 15 '16 at 13:47
  • $\begingroup$ @JohnHughes Also see Roman83's answer below. $\endgroup$ – Rohan Dec 15 '16 at 13:49
  • $\begingroup$ Right: Roman83 skips the same step that you do. That doesn't make it right. :) $\endgroup$ – John Hughes Dec 15 '16 at 13:51
  • 1
    $\begingroup$ Also note that your conclusion that $x^3 + y^3 + z^3 = 3xyz$ is equivalent to $x+y+z = 0$ is simply false: consider the case $x = y = z = 1$. $\endgroup$ – John Hughes Dec 15 '16 at 15:52
4
$\begingroup$

If you set $X=\log a$, $Y=\log b$ and $Z=\log c$ (any base you like), your condition becomes easily $$ \frac{X^3+Y^3+Z^3}{XYZ}=3 $$ Now you can use the identity $$ X^3+Y^3+Z^3=(X+Y+Z)^3-3(X+Y+Z)(XY+YZ+ZX)+3XYZ $$ to get that $$ (X+Y+Z)\bigl((X+Y+Z)^2-3(XY+YZ+ZX)\bigr)=0 $$ The second factor can be written $$ X^2+Y^2+Z^2-XY-YZ-ZX $$ and we should consider the quadratic form having as matrix $$ A=\begin{bmatrix} 1 & -1/2 & -1/2 \\ -1/2 & 1 & -1/2 \\ -1/2 & -1/2 & 1 \end{bmatrix} $$ Since $$ \det[1]=1>0, \qquad \det\begin{bmatrix}1 & -1/2 \\ -1/2 & 1\end{bmatrix}=3/4>0 \qquad \det A=0 $$ the quadratic form is positive semidefinite. Its null space contains the vector $[1\;1\;1]^T$, so we can conclude that your condition implies $$ X+Y+Z=0\qquad\text{or}\qquad X=Y=Z $$ Since by assumption $a$, $b$ and $c$ are pairwise distinct, we end with $X+Y+Z=0$.


Without quadratic forms, you can reason about $X^2+Y^2+Z^2-XY-YZ-ZX=0$ as follows. Since $Z\ne0$ by assumption, we can set $X=uZ$ and $Y=vZ$, so the equation becomes $$ u^2-uv+v^2-u-v+1=0 $$ and, solving with respect to $v$, $v^2-v(u+1)+u^2-u+1=0$, the discriminant is $$ (u+1)^2-4(u^2-u+1)=-3(u-1)^2 $$ so the equation has a solution only for $u=1$, which gives $v=1$. Therefore $X=Y=Z$.


Another “elementary” approach. Suppose $(X+Y+Z)^2=3(XY+YZ+ZX)$. Set $s=X+Y+Z$ and $p=XYZ$; then $X$, $Y$ and $Z$ are the roots of the equation $$ t^3-st^2+\frac{s^2}{3}t-p=0 $$ by Viète's formulas. We can complete the cube getting $$ \left(t-\frac{s}{3}\right)^3=p-\frac{s^3}{27} $$ which should have three real roots. This is impossible unless the roots are coincident, so $p=s^3/27$ and $X=Y=Z$.

$\endgroup$
  • $\begingroup$ Can't be understood If you don't know linear algebra, I suggest to replace it with a non-negative discriminant argument. $\endgroup$ – i9Fn Dec 15 '16 at 14:05
  • $\begingroup$ @i9Fn Agreed, but first of all I wanted to write a correct answer, which the others aren't. $\endgroup$ – egreg Dec 15 '16 at 14:10
  • $\begingroup$ I cannot express how much I appreciate this answer. I tried to write it myself, and realized I didn't know how. It definitely fills out the interesting (and more challenging) part of the original problem. $\endgroup$ – John Hughes Dec 15 '16 at 14:59
  • $\begingroup$ @JohnHughes Quadratic forms are a big fun. ;-) $\endgroup$ – egreg Dec 15 '16 at 15:39
  • $\begingroup$ Oh, yeah. Esp. over $\Bbb Z/ 2\Bbb Z$, where there's the Arf invariant. :) $\endgroup$ – John Hughes Dec 15 '16 at 15:42
1
$\begingroup$

Use $\log_a b=\frac{\ln a}{\ln b}$ $$\log _b a\cdot\log_c a +\log _a b\cdot\log_c b+\log _a c\cdot\log_b c=3$$ $$\frac{\ln a}{\ln b}\cdot \frac{\ln a}{\ln c}+\frac{\ln b}{\ln a}\cdot\frac{\ln b}{\ln c}+\frac{\ln c}{\ln a}\cdot\frac{\ln c}{\ln b}=3$$ $$\ln^3a+\ln^3b+\ln^3c=3(\ln a\ln b\ln c)$$ But $x^3+y^3+z^3=3xyz \Leftrightarrow x+y+z=0$

Then $\ln a+\ln b+\ln c=0$ $$\ln abc=0$$ Then $$abc=1$$

$\endgroup$
  • $\begingroup$ Your conclusion that $x^3 + y^3 + z^3 = 3xyz$ is equivalent to $x+y+z = 0$ is simply false: consider the case $x = y = z = 1$. (This possibility, in the problem, is ruled out by the assumption that $a,b,c$ are distinct, an assumption that your solution never uses.) $\endgroup$ – John Hughes Dec 15 '16 at 15:53
0
$\begingroup$

Got it!
$\log _b a\cdot\log_c a +\log _a b\cdot\log_c b+\log _a c\cdot\log_b c=3$
$$\frac{{(\log a)}^2}{\log b\cdot\log c} +\frac{{(\log b)}^2}{\log a\cdot\log c} +\frac{{(\log c)}^2}{\log a\cdot\log b} =3$$

$$\frac{{(\log a)}^3+{(\log b)}^3+{(\log c)}^3}{\log a\log b\log c} =3$$

$${(\log a)}^3+{(\log b)}^3+{(\log c)}^3=3\log a\log b\log c$$

This means $ \log a+\log b+\log c=0 \Rightarrow \log{abc}=0$
Hence, $abc=1$

$\endgroup$
  • $\begingroup$ The jump to "this means that..." could use a little justification; otherwise, you're good. $\endgroup$ – John Hughes Dec 15 '16 at 13:03
  • $\begingroup$ See egreg's answer to fill in the justification for the "this means that". $\endgroup$ – John Hughes Dec 15 '16 at 15:00

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.